Application of Block Analysis to the Study of Structure Polish Enterprises - Okupniak, Magdalena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
Intra- and interblock analysis has been used in agriculture, biology, medicine, engineering and the physical sciences. In this research I attempt to use block analysis in the filed of economics, to examine the structure of Polish enterprises and the relationships that exist between them. The study was based on such variables as: number of enterprises, persons employed and revenues. Data came from a Central Statistical Office of Poland publication entitled "Activity of non-financial enterprises in 2010".